Azapirones for Attention Deficit Hyperactivity Disorder: A Systematic Review - Matsui, Y.; Matsunaga, S.; Matsuda, Y.; Kishi, T.; Iwata, N. (Pharmacopsychiatry, 2016)
Introduction: No meta-analysis has evaluated azapirones (serotonin1A receptor partial agonists) as anxiolytics for attention deficit hyperactivity disorder (ADHD).Methods: Randomized controlled trials (RCTs) and single-arm trials published before October 27, 2015 were retrieved from major healthcare databases and clinical trial registries. Relative risk and 95% confidence intervals were calculated.Results: 5 RCTs (n=429) and 3 single-arm studies (n=70) were identified. 3 RCTs compared buspirone vs. methylphenidate in children/adolescents, one buspirone patches vs. placebo patches in children/adolescents, and one atomoxetine plus buspirone vs. atomoxetine vs. placebo in adults. The single-arm studies were buspirone trails in children/adolescents. All-cause discontinuation rates and adverse events did not differ between pooled buspirone and methylphenidate groups. No other meta-analyses of buspirone efficacy and safety vs. comparators were conducted due to insufficient data. 2 RCTs found no significant differences in parent and teacher ADHD-Rating Scale total scores between buspirone and methylphenidate, while one reported that methylphenidate improved parent and teacher ADHD-RS total scores vs. buspirone.Discussion: It remains unclear whether buspirone use has benefit for ADHD patients and therefore further evidence is needed for better clinical use of buspirone in patients with ADHD.
Keywords: azapirone; buspirone; attention deficit hyperactivity disorder; systematic review and meta-analysis; guidelines